Transformasi Limbah Vulkanik Gunung Lewotobi menjadi Filler Alternatif pada Beton Aspal Lapis Permukaan: Studi Eksperimen dengan Metode Marshall - Dewi Anastasia Ipah Wuwur; Vinsensius Budiman Pantas (TIN: Terapan Informatika Nusantara, 2026)
Volcanic activity at Mount Lewotobi produces large quantities of volcanic ash which, to date, has not been utilised to its full potential and tends to end up as environmental waste. On the other hand, the demand for fillers in asphalt concrete surface course (AC-WC) mixtures continues to rise in line with the development of road infrastructure, whilst the availability of conventional fillers is limited and dependent on specific materials. These circumstances highlight the need to develop sustainable alternative fillers based on local materials. This study aims to analyse the potential of volcanic ash from Mount Lewotobi as an alternative filler in surface-treated asphalt concrete (AC-WC) mixtures. The research focused on evaluating the physical characteristics of volcanic ash and the effect of its use on the Marshall parameters of the AC-WC mixture. The results of the study indicate that volcanic ash from Mount Lewotobi has a fineness that meets the requirements for use as a filler. The use of volcanic ash as an alternative filler produced stability, flow, VIM, VMA and VFB values that fell within the specification limits. At certain filler contents, volcanic ash was able to improve the stability and density of the mixture without significantly reducing its flexibility. The findings of this study take the form of technical recommendations for the use of volcanic ash from Mount Lewotobi as an alternative filler in AC-WC mixtures, which are expected to support the utilisation of local materials, resource efficiency and the implementation of sustainable road pavement construction, particularly in the East Nusa Tenggara region.